Fables - Lobel, Arnold (New York : Scholastic Inc, 1980)
Twenty original fables about an array of animal characters from crocodile to ostrich.
Keywords: Fables, American; Children's stories, American; Caldecott Medal; Animals -- Fiction; Fables